Effects of central-peripheral FMS on urinary retention after spinal cord injury: a pilot randomized controlled trial protocol - Dong, Lingyan; Tao, Xi; Gong, Cheng; Long, Yi; Xiao, Li; Luo, Yun; Wang, Maoyuan; Zhong, Yanbiao (Frontiers in Neurology, 2024)
Background Urinary retention is a common complication of spinal cord injury (SCI), which can seriously affect the quality of life of patients. Function magnetic stimulation (FMS) has been widely used in the recovery of neurological function in various diseases, but its application in urinary retention after SCI remains unclear. Therefore, we would like to conduct a pilot randomized controlled trial (RCT) to observe the feasible effect of FMS on urinary retention after SCI, to explore its mechanism of action. Method/design This is a single-center pilot RCT, which 60 patients with urinary retention after SCI will be selected, numbered in chronological order of hospitalization, and randomly divided into 4 groups using the random number table method, Groups A (control group), Group B, Group C, and Group D; Each group will receive the same conventional rehabilitation treatment. The whole intervention period 2 weeks and will be evaluated before and after treatment to collect data on residual bladder volume, functional near-infrared spectroscopy (fNIRS), changes in voiding condition, changes in surface electromyography (SEMG) values of pelvic floor muscle and quality of life scores (QoL). Study hypothesis We hypothesized that FMS for the treatment of urinary retention after SCI would have a significant clinical feasible effect;and that peripheral combined with central FMS would be more effective than single-site FMS for the treatment of urinary retention after SCI. Objective (1) To illustrate the clinical effectiveness of FMS in the treatment of urinary retention after SCI and to provide a new treatment modality for the patients; (2) Comparison of the differences in the efficacy of central and peripheral single FMS and combined central and peripheral FMS in the treatment of urinary retention after SCI; (3) To explore the central control mechanisms of bladder function recovery after SCI in conjunction with changes in fNIRS. Trial registration This study has been ethically approved by the Scientific and Ethics Committee of the First Affiliated Hospital of Gannan Medical university with approval number (LLSC-2022112401). It has been registered with the China Clinical Trials Registry with the registration number: ChiCTR2200067143.